Biocompatibility of submicron Bioglass® powders obtained by a top-down approach - Dörfler, Anja; Detsch, Rainer; Romeis, Stefan; Schmidt, Jochen; Eisermann, Claudia; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2014)
In this study in vitro bioactivity and biocompatibility of two submicron 45S5 Bioglass powders obtained by top-down processing have been evaluated and are compared to the as-received powder. Both submicron powders exhibited flake-like morphologies with lateral extensions of only a few microns; the flake thickness accounted for a few tens of nanometers. Enhanced in vitro bioactivity was found for the comminuted powders upon immersion in simulated body fluid. In vitro biocompatibility was evaluated by incubation of MG-63 osteoblast-like cells with various amounts (0-200 μg/mL) of the glass powders. Neither LDH-activity nor mitochondrial activity (WST-8) tests indicated cell toxicity. Increased mitochondrial activity was found for the submicron powders: incubation with high amounts revealed up to a threefold increase of osteoblast activity (ALP-activity). An overgrowth of the formed mineralized phase with phenotypical MG-63 cells was found by staining only for the submicron glasses. A distance ring is formed for the as-received powder. Superior bioactivity markers are found for shorter process times, that is, lower mass specific surface areas. This is attributed to the formation of carbonates during the comminution process. © 2013 Wiley Periodicals, Inc.
Keywords: in vitro bioactivity and biocompatibility; MG-63 cells; sub-micron particles; top-down production